Contending Ethnic Identities: An Issue to Pakistan’s Internal Security (The case of Karachi) - Umbreen Javaid and Rehana Saeed Hashmi (Journal of Political Studies, 2012)
Intra-ethnic conflict is an inevitable feature of plural societies. The presence of diverse ethnic groups poses an acute threat to Pakistan’s internal security. The uneven political, economic and social growth of these ethnies also accompanies the deteriorating situation especially in the city of Karachi. The deeply entrenched ethnic animosity, sectarian interests of religious elites and mutilated political leadership has plunged Karachi into a vortex of endless violence. The main argument of the present article is that there is a direct connection between political elite, ethnic parties and criminal gangs in Karachi. The article also highlighted various factors, influencing intra-ethnic warfare in Karachi.